Intensity-modulated whole abdominal radiotherapy after surgery and carboplatin/taxane chemotherapy for advanced ovarian cancer: phase I study - Rochet, Nathalie; Sterzing, Florian; Jensen, Alexandra; Dinkel, Julien; Herfarth, Klaus; Schubert, Kai; Eichbaum, Michael H. R.; Schneeweiss, Andreas; Sohn, Christof; Debus, Jürgen; Harms, Wolfgang (International journal of radiation oncology, biology, physics, 2010)
Purpose - To assess the feasibility and toxicity of consolidative intensity-modulated whole abdominal radiotherapy (WAR) after surgery and chemotherapy in high-risk patients with advanced ovarian cancer. - Methods and Materials - Ten patients with optimally debulked ovarian cancer International Federation of Gynecology and Obstetrics Stage IIIc were treated in a Phase I study with intensity-modulated WAR up to a total dose of 30 Gy in 1.5-Gy fractions as consolidation therapy after adjuvant carboplatin/taxane chemotherapy. Treatment was delivered using intensity-modulated radiotherapy in a step-and-shoot technique (n = 3) or a helical tomotherapy technique (n = 7). The planning target volume included the entire peritoneal cavity and the pelvic and para-aortal node regions. Organs at risk were kidneys, liver, heart, vertebral bodies, and pelvic bones. - Results - Intensity-modulated WAR resulted in an excellent coverage of the planning target volume and an effective sparing of the organs at risk. The treatment was well tolerated, and no severe Grade 4 acute side effects occurred. Common Toxicity Criteria Grade III toxicities were as follows: diarrhea (n = 1), thrombocytopenia (n = 1), and leukopenia (n = 3). Radiotherapy could be completed by all the patients without any toxicity-related interruption. Median follow-up was 23 months, and 4 patients had tumor recurrence (intraperitoneal progression, n = 3; hepatic metastasis, n = 1). Small bowel obstruction caused by adhesions occurred in 3 patients. - Conclusions - The results of this Phase I study showed for the first time, to our knowledge, the clinical feasibility of intensity-modulated whole abdominal radiotherapy, which could offer a new therapeutic option for consolidation treatment of advanced ovarian carcinoma after adjuvant chemotherapy in selected subgroups of patients. We initiated a Phase II study to further evaluate the toxicity of this intensive multimodal treatment.